Perancangan Protocol TCP/IP pada Jaringan Topologi Star dengan Metode Experimen pada Cisco Packet Tracer Versi 8.2.2 - Ira Zulfa; Rahmadi Asri; Kurnia Azmi (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
This research discusses the design and implementation of the TCP/IP protocol on a star topology network using Cisco Packet Tracer version 8.2.2. The main objective of this study is to analyze network performance and demonstrate that the star topology provides greater stability, easier management, and more efficient data communication compared to the bus topology previously used in the Faculty of Engineering Laboratory at Gajah Putih University. The research method applied is a simulation experiment by designing and configuring a network model consisting of virtual PCs, laptops, servers, and switches to represent the actual laboratory network environment. The testing process focuses on communication performance, connectivity, packet transmission, and network efficiency using the TCP/IP protocol. The experimental results show that host-to-host communication runs effectively, with a very low packet loss rate and acceptable delay levels. Furthermore, the star topology successfully minimizes data collisions, improves network reliability, and simplifies troubleshooting processes compared to the bus topology. In conclusion, the implementation of TCP/IP on a star topology network can serve as an effective alternative for improving network quality, stability, and management efficiency in educational laboratory environments.